New Molecular Data in the Truffle-like Fungus, Aroramyces herrerae, Reveal a Novel Cryptic Ancestral Taxon, Pterosporomyces herrerae gen. nov. & comb. nov. (Trappeacea, Phallales) (Global Journal of Science Frontier Research, 2021)
Recently, Aroramyces herrerae was described based on morphology, ecology, and taxonomically placed in the family Hysterangiaceae (Hysterangiales). However, a DNA analysis revealed that A. herrerae belongs to a new sequestrate cryptic genus, Pterosporomyces, in the family Trappeaceae (Phallales), nested with Restingomyces reticulatus and Phalobata alba and jointly forming a basal clade of Phallales with strong statistical support. Pterosporomyces herrerae gen. nov & comb. nov. is characterized by an olive green to brown gleba and wing spores (utriculum) up to 6 µm broad and its ITS and ATP6 variation. Pterosporomyces is similar in morphology to Restingomyces but differs by the spore ornamentation been utriculate in the former and alveolate in the latter.